Autogenic Relaxation is Effective in Reducing Blood Pressure in Elderly People who Experience Hypertension - Risdiana Melinda Naibaho; Wiwik Dwi Arianti (GLOBAL HEALTH SCIENCE GROUP, 2025)
Hypertension in the elderly is a degenerative disease health problem that tends to worsen over time and can increase the risk of various cardiovascular diseases. Autogenic relaxation, which involves deep breathing and self-suggestion to calm the body, is expected to help lower blood pressure. This study aims to explore the effects of autogenic relaxation techniques in lowering blood pressure in the elderly with hypertension. The research method used was pre-experimental with a One Group Pretest-Posttest Design. The population of this study were all active elderly at Posyandu for the elderly of Bintang Village in the working area of UPT Puskesmas Batang Beruh who experienced hypertension 34 samples with purposive sampling technique to collect data with measuring instruments using blood pressure meters according to SOP and observation sheets. The average decrease in blood pressure after intervention was 137.56 mmHg with an average difference in systole reduction of 15.41 mmHg, diastole blood pressure after intervention was 83.41 mmHg with an average difference in diastolic reduction of 9.26 mmHg. Statistical tests using Paired Sample t-test resulted in a p value <0.01, which indicates significance at the 95% level of significance (α = 0.05). Autogenic relaxation is effective in reducing blood pressure in the elderly who experience hypertension.